The Effects Of Engklek And Egrang Batok Games On Dynamic Balance In Children Aged 9–10 - Pradani, Aliffia Aura Putri; Awanis, Almas; Ariyanti, Lilik (FISIO MU: Physiotherapy Evidences, 2026)
Introduction: Dynamic balance is a crucial ability in children's motor development, especially at the elementary school age. Traditional games such as engklek (hopscotch), egrang batok kelapa (coconut shell stilts) are believed to provide effective stimuli for enhancing children's balance function. To determine the difference in effects between the traditional games engklek and egrang batok kelapa on improving dynamic balance in children aged 9–10 years. Methods: This study is a quasi-experiment with a pretest-posttest two-group design. The population consisted of 70 students, and the sample included 41 students from SDN Kuwonharjo, Magetan, aged 9–10 years, divided into two groups: a control group with standard training dosage and an intervention group with modified training dosage. Measurements were conducted using the Balance Beam Test (BBT) before and after the intervention. Results: There was a significant improvement in dynamic balance in both groups (p < 0.05). However, the difference test showed no significant difference between the two groups (p = 0.416), indicating relatively similar effectiveness between engklek and egrang batok kelapa. Conclusion: Both traditional games, engklek and egrang batok kelapa, are equally effective in improving dynamic balance in children aged 9–10 years. These games can serve as enjoyable, practical physiotherapy alternatives in school settings.